Pembinaan Masyarakat Tentang Penerapan Perilaku Hidup Bersih dan Sehat Di Desa Kolam Kecamatan Percut Sei Tuan - Nixson Manurung (Pusat Riset dan Inovasi Nasional, 2021)
Health is what everyone is looking for. According to the World Health Organization (WHO) health is a state of complete physical, mental and social well-being and not merely the absence of disease. One of the ways to keep the body in good health is to live a clean and healthy lifestyle. The indicators used in PHBS Indonesia are efforts to prevent communicable diseases (behavior indicators of washing hands with soap, using clean water, using healthy latrines; and eradicating mosquito larvae) and non-communicable diseases (indicators of consuming fruits and vegetables; doing physical activity; and not smoking in the house), as well as efforts to improve the health of mothers and children (indicators of deliveries with health personnel, exclusive breastfeeding, and weighing toddlers). The Basic Health Research (Riskesdas) in 2007, 2013 and 2018 showed that the proportion of households that have practiced PHBS over the last ten years has increased by around 28%. A detailed description of the five-year PHBS proportion, namely 11.2% (2007) to 23.6% (2013) and then 39.1% (2018). The method used was descriptive observational with 30 family participants in Kola Village, Percut Sei Tuan District, Deli Serdang. The PkM team provided the material in question 1) Definition of healthy clean living behavior (PHBS), 2) Benefits of PHBS 3) Criteria for healthy households, and 4) How to implement PHBS. The results after the implementation of the activity 1) The definition of healthy clean living behavior (PHBS) is more dominated by either 28 people, 2) The benefits of PHBS are more dominated by both 26 people, 3) The criteria for healthy households are more dominated by either 28 people, 4) In general, the method of implementing PHBS is well mastered by 18 people. Increased knowledge and skills of participants because the community has a great desire to treat and prevent illness in family members at home.